New iterative method of solving nonlinear equations in fluid mechanics - Paliivets, Maksim; Bakshtanin, Alexander; Benin, Dmitriy M.; Andreev, E.; Snezhko, V.L. (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents the results of applying a new iterative method to linear and nonlinear fractional partial differential equations in fluid mechanics. A numerical analysis was performed to find an exact solution of the fractional wave equation and fractional Burgers` equation, as well as an approximate solution of fractional KdV equation and fractional Boussinesq equation.
Keywords: Adomian decomposition method (ADM); earthquake; filtration; fluid mechanics; iterative methods; nonlinear fractional partial differential equations; porous medium